Physical development of athletes of cyclic sports specializing in athletics and cross-country skiing - Fedulova, D. V.; Serova, N. B. (Theory and Practice of Physical Culture, 2022)
Objective of the study is a comparative assessment of the development of physical qualities and anthropometric indicators of athletes specializing in athletics and cross-country skiing.